2021
DOI: 10.1007/s00410-021-01807-3
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of deep Tunguska Basin sills, Siberian Traps: correlations and potential implications for the end-Permian environmental crisis

Abstract: A vast portion of the plumbing system of the Siberian Traps Large Igneous Province (STLIP) is emplaced in the Tunguska Basin, where borehole data reveal ubiquitous and abundant sills with great lateral extension. These intrusions intersect Cambrian–Ordovician evaporite, carbonate and siliciclastic series, and locally coal-bearing Permian host rocks, with a high potential for thermogenic gas generation. Here we present new geochemical data from 71 magmatic and 4 sedimentary rock samples from the Tunguska Basin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 105 publications
(324 reference statements)
0
10
0
2
Order By: Relevance
“…caused by varying degrees of assimilation of crustal sedimentary rocks (including evaporites) by the Siberian Traps magmas during their emplacement, as has been suggested by others (Lightfoot et al, 1990;Wooden et al, 1993;Callegaro et al, 2021).…”
Section: Origin Of Halogens In Basalts and Dolerites Of The Siberian Traps Large Igneous Provincementioning
confidence: 68%
See 1 more Smart Citation
“…caused by varying degrees of assimilation of crustal sedimentary rocks (including evaporites) by the Siberian Traps magmas during their emplacement, as has been suggested by others (Lightfoot et al, 1990;Wooden et al, 1993;Callegaro et al, 2021).…”
Section: Origin Of Halogens In Basalts and Dolerites Of The Siberian Traps Large Igneous Provincementioning
confidence: 68%
“…The brine's ability to flow into the sill is supported by observations of veins and fissures in the sill filled in with salt precipitates 5-8 m from the contacts. In addition, high chlorine concentration on the rims of biotites in sills in the Lower Tunguska area have been interpreted as being due to chlorine transfer via a hydrous fluid (Heimdal et al, 2019;Callegaro et al, 2021) as observed for aureoles surrounding mafic sills at Norilsk (Pang et al, 2013).…”
Section: Locationmentioning
confidence: 95%
“…The ashes show intermediate to acidic chemical compositions, plotting in the field of basaltic andesite, trachy-andesite and rhyolite/dacite (Fig. 6a), and are chemically distinct from volcanic rocks originating from the STLIP (Callegaro et al, 2021;Reichow et al, 2005;Sibik et al, 2015;Sobolev et al, 2009). In addition, a mid-oceanic ridge basalt (MORB)-normalized trace element (Th vs. Nb) discriminant plot (Saccani et al, 2015(Saccani et al, , 2018 of the volcanic ashes from the Pingtang syncline suggests that they originate from a continental margin volcanic arc tectonic setting (Fig.…”
Section: Provenance Of Volcanic Hg Inputmentioning
confidence: 99%
“…0.40 Ma, building the vast network of sills in the Tunguska Basin. These tholeiitic magmas were produced by shallower and extensive melting of a mixed peridotitic-pyroxenitic mantle (Sobolev et al, 2011;Callegaro et al, 2021). Renewed extrusive activity is recognized from 251.48 ± 0.09 Ma, marking the beginning of the third phase of the Siberian Traps.…”
Section: Introductionmentioning
confidence: 99%
“…The beginning of the second (intrusive) phase is considered as the deadly subinterval of the Siberian Traps (Burgess et al, 2017), since it coincides with the beginning of the extinction horizon at Meishan (251.94 ± 0.04 Ma; Burgess et al, 2014), Dongpan and Penglaitan (251.94 ± 0.03 Ma and 251.98 ± 0.03 Ma; Baresel et al, 2017), China. Even if these tholeiitic magmas were probably volatile poor (Sibik et al, 2015), the interaction between the sills and the sedimentary host-rocks (i.e., evaporites, carbonates, marlstones, and coal) likely produced large amounts of thermogenic carbon, sulfur and halocarbon species (Svensen et al, 2018;Callegaro et al, 2021;Sibik et al, 2021).…”
Section: Introductionmentioning
confidence: 99%